Core technology development trends of quantum industry and global market growth trends - Kim, Jong-Yun (Edelweiss Applied Science and Technology, 2025)
This study analyzes the advantages of three key technologies in the quantum industry (quantum computers, quantum cryptography, and quantum sensors) in Chapter 2. It analyzes the development trends of quantum technologies and the global market growth trends for each technology, such as quantum computers, which have been accelerating since around 2012; quantum cryptography, which is replacing the existing digital cryptographic communication network using QKD services; and quantum sensors, which provide the foundation for the realization of quantum computer/quantum cryptography communication technology based on the results of precise measurement of quantum states in Chapter 3. The study concludes by presenting the process of a full-fledged quantum industry in Korea and ways to improve the performance of quantum computers in Chapter 4. In order to dramatically improve the performance of quantum computers, it is necessary to understand the materials of the superposition of the two quantum states and to develop a technology development strategy that can address these shortcomings at an early stage.